Exosomal glypican-1 discriminates pancreatic ductal adenocarcinoma from chronic pancreatitis. Issue 7 (July 2022) - Moutinho-Ribeiro, P.; Adem, B.; Batista, I.; Silva, M.; Silva, S.; Ruivo, C.F.; Morais, R.; Peixoto, A.; Coelho, R.; Costa-Moreira, P.; Lopes, S.; Vilas-Boas, F.; et al.
Abstract: Background and aims: Pancreatic ductal adenocarcinoma (PDAC) diagnosis can be difficult in a chronic pancreatitis (CP) background, especially in its mass forming presentation. We aimed to assess the accuracy of glypican-1-positive circulating exosomes (GPC1 + crExos) to distinguish PDAC from CP versus the state-of-the-art CA 19–9 biomarker. Methods: This was a unicentric prospective cohort. Endoscopic ultrasound with fine-needle aspiration or biopsy and blood tests (GPC1 + crExos and serum CA 19–9) were performed. Results: The cohort comprised 60 PDAC and 29 CP (7 of which mass forming - MF) patients. Median levels of GPC1 + crExos were significantly higher in PDAC (99.7%) versus CP (28.4%; p <0.0001) with an AUROC of 0.96 with 98.3% sensitivity and 86.2% specificity for a cut-off of 45.0% ( p <0.0001); this outperforms CA 19–9 AUROC of 0.82 with 78.3% sensitivity and 65.5% specificity at a cut-off of 37 U/mL ( p <0.0001). The superiority of% GPC1+crExos over CA 19–99 in differentiating PDAC from CP was observed in both early (stage I) and advanced tumors (stages II-IV). Conclusion: Levels of GPC1 + crExos coupled to beads enable differential diagnosis between PDAC and CP including its mass-forming presentation.